Spontaneous peeled ileal giant lipoma caused by lower gastrointestinal bleeding: A case report. Issue 51 (December 2017) - Kim, Jung Ho; Yoon, Hyun Hwa; Jeong, Seok Hoo; Woo, Hyun Sun; Lee, Won-Suk; Choi, Seung Joon; Kim, Seog Gyun; Ha, Seung Yeon; Kwon, Kwang An
Abstract: Rationale: Gastrointestinal subepithelial tumors (SETs) with endoscopic features such as ulceration, a red color change, a peeled mucosal layer, and spontaneous bleeding could have malignant potential. However, we encountered a case of a lipoma that presented features different from the generally known features of gastrointestinal SETs. Therefore, we report an interesting rare case of a terminal ileal giant lipoma with a unique feature of spontaneous peeled ulceration on the surface on endoscopy that caused gastrointestinal bleeding. Patient: An 82-year-old woman with a 1-week history of abdominal pain and hematochezia presented to our hospital. Diagnoses: Ileocolonoscopy revealed a SET with a peeled surface and erythematous and ulcerative mucosal changes as well as exposed a submucosal mass at the terminal ileum. Macroscopically, the lesion appeared as a yellowish pedunculated polypoid mass measuring 3 × 2 cm with a peeled mucosal ulceration. Histopathological findings revealed a submucosal lipoma of the terminal ileum. Intervention: We thought that the endoscopic finding indicated malignant SETs or those with malignant potential rather than benign SETs. Therefore, the patient underwent an elective laparoscopic ileocecectomy. Lessons: We encountered a lipoma that did not present with the typical features of gastrointestinal SETs. Our findings suggest that clinicians should consider that benign SETs in the terminal ileum may present with various endoscopic findings similar to those of malignant SETs, which can cause fatal symptoms and signs.